Country Institutional Profiles: Unlocking Entrepreneurial Phenomena - Busenitz, Lowell W.; Gómez, Carolina; Spencer, Jennifer W. (Academy of Management Journal, 2000)
This study introduces and validates a measure of country institutional profile for entrepreneurship consisting of regulatory, cognitive, and normative dimensions. Subscales based on data from six countries show reliability, discriminant validity, and external validity. The instrument provides researchers with a valuable resource for exploring why entrepreneurs in one country may have a competitive advantage over entrepreneurs in other countries and how specific country-level institutional differences contribute differently to levels and types of entrepreneurship.